Games and Sports in Ancient Rural Backward Life and Culture - Chattopadhyay, Dr. Arunava (IJRDO - Journal of Social Science and Humanities Research, 2017)
Health means physical, mental and spiritual health. To keep health well games and sports are essential. From very ancient time there was culture of games and sports in civilised society. Competitions, festivals on physical culture were held in civilised countries. People believe that healthy body is the temple of living god. It was prominent in folk life and backward communities. In West Bengal dance, jump, run were main parts of folk festivals. By these developments of body, mind and spirit were made. So these were very popular. There was no material gain, but there was joy in physical culture. There was no need of costly equipments for such games and sports. In West Bengal, ancient rural games among backward communities are of two types - a) Indoor games b) Outdoor games.